2020
DOI: 10.1515/pjbr-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

A study on an applied behavior analysis-based robot-mediated listening comprehension intervention for ASD

Abstract: Autism spectrum disorder (ASD) is a lifelong developmental condition that affects an individual’s ability to communicate and relate to others. Despite such challenges, early intervention during childhood development has shown to have positive long-term benefits for individuals with ASD. Namely, early childhood development of communicative speech skills has shown to improve future literacy and academic achievement. However, the delivery of such interventions is often time-consuming. Socially assistive robots (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…[51] NAO Social interaction: General Getting into interaction [9], [11], [16], [18], [20], [31], [35], [45], [46], [53] Darwin-Mini, ROMO, Kaspar, KiliRo, iRobiQ, CARO, Pleo, Keepon, Labo-1, Autonomous social robot, Sphero Turn-taking [16], [21], [32], [35], [43], [46], [52], [56] Zoomer dog, Darwin-Mini, ROMO, NAO, Rovio, Labo-1, ZECA, Autonomous social robot Child's engagement in an activity [23], [26], [40], [43], [52] Darwin-Mini, ROMO, SAM, ZECA, NAO Following / imitating movements [9], [20], [46], [52], [60] Kaspar, FACE, Labo-1, NAO, ZECA Social attention abilities [11], [15], [39], [56] NAO, Keepon Social interaction [31], [41], [53] KiliRo, Pleo, NAO Social abilities [35] Autonomous social robot Sensory processing skills [23] Darwin-Mini, ROMO Basic eye contact [30] iRobiQ, CARO Conversational interaction [31] Pleo Socio-emotional behaviors [23] Darwin-Mini, ROMO Social interaction: Focus on self-initiated interaction [16], [41],…”
Section: Skill Groupmentioning
confidence: 99%
See 4 more Smart Citations
“…[51] NAO Social interaction: General Getting into interaction [9], [11], [16], [18], [20], [31], [35], [45], [46], [53] Darwin-Mini, ROMO, Kaspar, KiliRo, iRobiQ, CARO, Pleo, Keepon, Labo-1, Autonomous social robot, Sphero Turn-taking [16], [21], [32], [35], [43], [46], [52], [56] Zoomer dog, Darwin-Mini, ROMO, NAO, Rovio, Labo-1, ZECA, Autonomous social robot Child's engagement in an activity [23], [26], [40], [43], [52] Darwin-Mini, ROMO, SAM, ZECA, NAO Following / imitating movements [9], [20], [46], [52], [60] Kaspar, FACE, Labo-1, NAO, ZECA Social attention abilities [11], [15], [39], [56] NAO, Keepon Social interaction [31], [41], [53] KiliRo, Pleo, NAO Social abilities [35] Autonomous social robot Sensory processing skills [23] Darwin-Mini, ROMO Basic eye contact [30] iRobiQ, CARO Conversational interaction [31] Pleo Socio-emotional behaviors [23] Darwin-Mini, ROMO Social interaction: Focus on self-initiated interaction [16], [41],…”
Section: Skill Groupmentioning
confidence: 99%
“…However, another study [64] even recommended a familiarisation phase, where the children can freely explore the robot in order to reduce anxiety levels and make the robot more attractive. Similarly, the next study [40] suggested the therapist should familiarize the participants with the intervention and the robot.This was due to the fact that at the beginning of the interventions, 2 from 3 participants were not responding to the robot. Researchers observed that initial human prompts helped the children understand how to interact with the robot.…”
Section: ) Participants' Experience With Robotsmentioning
confidence: 99%
See 3 more Smart Citations